Wahrheitsspiele: Zu den Interviewformaten André Müllers und Moritz von Uslars. Issue 1 (2nd January 2016) - Hoffmann, Torsten
Abstract : The point of departure for this article is that in interviews authenticity and artificiality find themselves in a productive tension. This tension is taken to an extreme in the interview formats of André Müller and Moritz von Uslar. Common to both of them is that the questioner becomes the real star of these interviews. Müller achieves this, insofar as he consistently aligns the discussions to his own psychological interests and thus aims at an exchange of roles within the conventional asymmetric interview model. In addition (as in Uslar's case as well), there is an attempt, with the aid of subtexts, to draw the reader's focus to the process of the interview and thereby heighten the reader's genre awareness. Whereas the most important cultural benchmark for Müller's interviews is psychoanalysis, for Uslar it is sporting events. Portraits emerge not from substantial questions, but rather through the playful, often nonverbal exchanges of the interview actors. It is not what the interviewee has to say that is of interest, but rather how he reacts to the unconventional rules of the game in this format. The result is a degree of self-reflexivity that has never before been reached in the history of interviews.